The Role of the Internet in the Development of Marketing and Electronic Services in Business - Terziu, Hysni (European Journal of Economics and Business Studies, 2020)
Internet marketing and e-services are considered the latest areas of research, which represent a strategic importance for businesses that have directed their efforts towards e-marketplace. Studies have shown that online consumer behavior differs from consumer behavior in the traditional marketplace. On the other hand, managers seem to have a good understanding of the needs of consumers to meet them effectively and efficiently in the electronic environment. Few things have dramatically and instantly affected our lives and the way many businesses operate more than the development of the internet. The ways in which some marketing activities are carried out have changed since businesses turned to trading. The Internet offers opportunities for an organization to grow its business in an efficient and practical way. This means that the internet can be used to conduct marketing research, reach new markets, better serve customers, distribute products faster, solve customer problems, and communicate more efficient with business partners. The benefits of online marketing include improved information flow, new products and customer service, improved availability, and better market transparency. To design and implement a successful e-marketing program, a number of theories, applications, and technologies need to be carefully analyzed and understood. In this paper we will examine the best ways of Internet marketing for business success. The main objective of this article is to understand the impact of the Internet on various areas of marketing, such as product development and service delivery, promotion, pricing and channel distribution. The paper shows that when manufacturers connect directly with customers and shorten distribution channels, inefficiencies can be eliminated, product delivery time can be reduced, and manufacturers can build closer relationships with customers. Consumers use the internet to reduce costs, find otherwise unavailable products, or increase the ease of their purchase. Online customers expect simple, understandable and secure ordering and payment systems. Consumers want confidence that orders will be fulfilled immediately. E-commerce creates value for consumers in many ways. Consumers are treated as a market of one. They may have access to a greater variety of products, often at lower prices. The study suggests that businesses need to pay special attention to the impacts of the Internet and its uses in marketing to be successful and profitable.
Keywords: Internet, Marketing, Business, Companies, Strategy, Consumers, Success